2009
DOI: 10.1002/jcb.22126
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic study of saikosaponin‐d (Ssd) on suppression of murine T lymphocyte activation

Abstract: Saikosaponin-d (Ssd) is a triterpene saponin derived from the medicinal plant, Bupleurum falcatum L. (Umbelliferae). Previous findings showed that Ssd exhibits a variety of pharmacological and immunomodulatory activities including anti-inflammatory, anti-bacterial, anti-viral and anti-cancer effects. In the current study we have investigated the effects of Ssd on activated mouse T lymphocytes through the NF-kappaB, NF-AT and AP-1 signaling pathways, cytokine secretion, and IL-2 receptor expression. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 49 publications
(45 reference statements)
0
60
0
Order By: Relevance
“…IL-2 expression can be up-regulated when ERK is activated, while the opposite response is observed when ERK activity is inhibited [Koike et al, 2003]. JNK could phosphorylate c-jun, a member of the AP-1 transcriptional factor family which has been shown to be induced upon T cell activation and involved in IL-2 gene transcriptional activity [Li-Weber et al, 2005;Wong et al, 2009]. Inhibition of p38 kinase can prevent the expression of IL-2, which means p38 kinase is essential for T-cell activation [Zhang et al, 1999].…”
Section: Discussionmentioning
confidence: 97%
“…IL-2 expression can be up-regulated when ERK is activated, while the opposite response is observed when ERK activity is inhibited [Koike et al, 2003]. JNK could phosphorylate c-jun, a member of the AP-1 transcriptional factor family which has been shown to be induced upon T cell activation and involved in IL-2 gene transcriptional activity [Li-Weber et al, 2005;Wong et al, 2009]. Inhibition of p38 kinase can prevent the expression of IL-2, which means p38 kinase is essential for T-cell activation [Zhang et al, 1999].…”
Section: Discussionmentioning
confidence: 97%
“…In other words, the therapeutic effects of SSD on liver fibrosis and cirrhosis may be attributed to its anti-inflammatory pharmacological activity. At the cellular and molecular level, it has been reported that SSD suppresses T cell activity through inhibition of the NF-κB signaling pathway and COX-2 expression (31,47). Since SSD inhibits COX-2 activity, chronic inflammation, liver fibrosis and cirrhosis, which are relevant to HCC, it is reasonable to characterize SSD as a potential chemopreventive or chemotherapeutic agent against heparocarcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Although the biological activity of certain Bupleurum essential oils and saponins had been compiled early in 2006, [10] a vast body of scientific literature on the pharmacological activity of other species and classes of secondary metabolites have since emerged. [63,[66][67][68][69][70][71][72][73][74] A summary of some of the relevant literature is given in Table 1 and discussed in the following section.…”
Section: Pharmacological Properties Of Bupleurummentioning
confidence: 99%
“…The inhibitory effect of ssD on phorbol myristate acetate (PMA)-induced T-cell activation was associated with down-regulation of NF-kB signalling. In addition, ssD at 15 mm concentration decreased the production of proinflammatory cytokines IL-6, tumour necrosis factor (TNF)-a and interferon (IFN)-g. [68] The immunomodulatory effect of some B. fruticosum extracts and isolated compounds has been investigated extensively against several markers of the immune response. [98,101] A petroleum ether extract (100 mg/ml) caused 80-100% release of IL-1b and IL-6 and prostaglandin (PG) E2 synthesis in human monocytes.…”
Section: Immunomodulatory Activitymentioning
confidence: 99%